The perils of planning strategies to increase vitamin C content in plants: Beyond the hype - Terzaghi, Mattia; De Tullio, Mario C. (Frontiers in Plant Science, 2022)
Ever since the identification of vitamin C (ascorbic acid, AsA) as an essential molecule that humans cannot synthesize on their own, finding adequate dietary sources of AsA became a priority in nutrition research. Plants are the main producers of AsA for human and other non-synthesizing animals. It was immediately clear that some plant species have more AsA than others. Further studies evidenced that AsA content varies in different plant organs, in different developmental stages/environmental conditions and even within different cell compartments. With the progressive discovery of the genes of the main (Smirnoff-Wheeler) and alternative pathways coding for the enzymes involved in AsA biosynthesis in plants, the simple overexpression of those genes appeared a suitable strategy for boosting AsA content in any plant species or organ. Unfortunately, overexpression experiments mostly resulted in limited, if any, AsA increase, apparently due to a tight regulation of the biosynthetic machinery. Attempts to identify regulatory steps in the pathways that could be manipulated to obtain unlimited AsA production were also less successful than expected, confirming the difficulties in “unleashing” AsA synthesis. A different approach to increase AsA content has been the overexpression of genes coding for enzymes catalyzing the recycling of the oxidized forms of vitamin C, namely monodehydroascorbate and dehydroascorbate reductases. Such approach proved mostly effective in making the overexpressors apparently more resistant to some forms of environmental stress, but once more did not solve the issue of producing massive AsA amounts for human diet. However, it should also be considered that a hypothetical unlimited increase in AsA content is likely to interfere with plant development, which is in many ways regulated by AsA availability itself. The present review article aims at summarizing the many attempts made so far to improve AsA production/content in plants, evidencing the most promising ones, and at providing information about the possible unexpected consequences of a pure biotechnological approach not keeping into account the peculiar features of the AsA system in plants.